Delayed Interval Delivery in Preterm Premature Rupture of Membranes in Dichorionic Triamniotic Triplets: Ethical Considerations for Maternal Health Case Report - Ali Hosiani; James Brown; Indika T. Alahakoon (Hindawi Limited, 2022)
Background. Although there are numerous studies on delayed interval delivery in twins, this study is one of few reporting on preterm premature rupture of membranes in triplets and even fewer on dichorionic triamniotic triplet twins. The case presented here highlights the important interplay between informed consent and patient autonomy. Case Presentation. A 37-year-old woman gravida 1, para 0 with a dichorionic triamniotic triplet pregnancy experienced preterm premature rupture of membranes of the singleton triplet at 15 weeks and six days of gestation. Delayed interval delivery was offered to the parents, who chose to continue the pregnancy while acknowledging the risks for maternal and foetal health. The patient was treated with prophylactic intravenous antibiotics and discharged on oral antibiotics after an eight-day admission. Two days after being discharged, she was readmitted with clinical signs of chorioamnionitis. Within six hours, the preterm premature rupture of membranes singleton was delivered. Three days later, she again presented to the hospital with preterm premature rupture of membranes of one of the dichorionic twins. After discussion with the maternal foetal medicine team, the parents chose to terminate the pregnancy. Delayed interval delivery was not successful in this patient, and it is unclear at which gestational age it is too early to offer expectant management. Conclusions. The case affirmed the very poor foetal survival rate when the first delivery occurs at under 20 weeks' gestation. A standardised management of delayed interval delivery should be established to assist with consistent parental counselling.